A 2000 year long seasonal record of floods in the southern European Alps. Issue 15 (2nd August 2013) - Wirth, Stefanie B.; Gilli, Adrian; Simonneau, Anaëlle; Ariztegui, Daniel; Vannière, Boris; Glur, Lukas; Chapron, Emmanuel; Magny, Michel; Anselmetti, Flavio S.
Abstract: [1] Knowledge of past natural flood variability and controlling climate factors is of high value since it can be useful to refine projections of the future flood behavior under climate warming. In this context, we present a seasonally resolved 2000 year long flood frequency and intensity reconstruction from the southern Alpine slope (North Italy) using annually laminated (varved) lake sediments. Floods occurred predominantly during summer and autumn, whereas winter and spring events were rare. The all‐season flood frequency and, particularly, the occurrence of summer events increased during solar minima, suggesting solar‐induced circulation changes resembling negative conditions of the North Atlantic Oscillation as controlling atmospheric mechanism. Furthermore, the most extreme autumn events occurred during a period of warm Mediterranean sea surface temperature. Interpreting these results in regard to present climate change, our data set proposes for a warming scenario, a decrease in summer floods, but an increase in the intensity of autumn floods at the South‐Alpine slope. Key Points: Varved S‐Alpine lake sediments provide a 2 kyr‐long seasonal record of floods Solar‐induced meridional shifts of the Westerlies control the flood occurrence High solar activity/climate warming lead to fewer summer and autumn floods